(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The study examines the impact of using artificial intelligence in e-stores on consumer behavior. The study highlights the importance of artificial intelligence in improving the online shopping experience, by providing personalized recommendations and analyzing purchasing patterns to better meet consumer needs. Artificial intelligence techniques such as natural language processing, deep learning, and augmented reality are used to provide a distinctive experience that contributes to increasing customer loyalty and raising conversion rates. The study indicates that artificial intelligence can automate many tasks, such as inventory management and order processing, which contributes to reducing costs and improving operational efficiency. Artificial intelligence also plays an important role in enhancing e-commerce security, as it can detect fraud and protect personal data. The study included the impact of AI-supported shopping practices on customers’ functional, financial, social, and emotional values. The results of previous studies reviewed indicate the positive impact of artificial intelligence on the efficiency of marketing methods, and raising the competitive advantage of e-stores by improving the mental image and increasing profitability.